2002
DOI: 10.1161/01.res.0000019540.41697.60
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Gene Therapy for Experimental Critical Limb Ischemia

Abstract: Abstract-Recent studies suggest the possible therapeutic effect of intramuscular vascular endothelial growth factor (VEGF) gene transfer in individuals with critical limb ischemia. Little information, however, is available regarding (1) the required expression level of VEGF for therapeutic effect, (2) the related expression of endogenous angiogenic factors, including fibroblast growth factor-2 (FGF-2), and (3) the related adverse effects due to overexpression of VEGF.To address these issues, we tested effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
121
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(133 citation statements)
references
References 26 publications
9
121
1
Order By: Relevance
“…4,5 Sendai virus (SeV), also a member of the Paramyxoviridae, infects most mammalian cells and directs highlevel expression not only in cultured cells but also in experimental animals of the genes within its genome that have been exploited for therapeutic use and vaccination. [6][7][8][9][10] A strong potential of NDV as a vaccine vector was also demonstrated. 11 SeV and most of the other mononegaviruses replicate independent of cellular nuclear functions and do not have a DNA phase in their lifecycle, and therefore are not considered to present a high risk of cell transformation by integration of the viral genetic information into the cellular genome.…”
Section: Introductionmentioning
confidence: 95%
“…4,5 Sendai virus (SeV), also a member of the Paramyxoviridae, infects most mammalian cells and directs highlevel expression not only in cultured cells but also in experimental animals of the genes within its genome that have been exploited for therapeutic use and vaccination. [6][7][8][9][10] A strong potential of NDV as a vaccine vector was also demonstrated. 11 SeV and most of the other mononegaviruses replicate independent of cellular nuclear functions and do not have a DNA phase in their lifecycle, and therefore are not considered to present a high risk of cell transformation by integration of the viral genetic information into the cellular genome.…”
Section: Introductionmentioning
confidence: 95%
“…(12) It is not clear whether locally delivered therapeutic agents can improve the vascularization of ischemic animal models (13,14) or inhibit bone resorption in SAON. (15) It has been shown that histopathologically proven destructive repair in SAON is characterized by continuous marrow edema closely coupled with persistent bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…tissue necrosis) in old animals 8,11 and in animals with compromised immune system. 9,12 Diminished angiogenesis in these animal models corresponded with decreased expression of VEGF. 8,9,13 Interestingly, substituting VEGF by exogenously delivered protein or gene has not shown therapeutic benefit in either aged mice 11 or in balb/c mice, 12 unlike in other mouse models.…”
Section: Introductionmentioning
confidence: 89%
“…9,12 Diminished angiogenesis in these animal models corresponded with decreased expression of VEGF. 8,9,13 Interestingly, substituting VEGF by exogenously delivered protein or gene has not shown therapeutic benefit in either aged mice 11 or in balb/c mice, 12 unlike in other mouse models. 9 Similarly, VEGF refractory, severe hindlimb ischemia was also reported in mice deficient of endothelial nitric oxide synthase (ecNOS-KO).…”
Section: Introductionmentioning
confidence: 89%